A new proposal for the quantification of homogeneity in the wort boiling process. Issue 2 (19th March 2015) - Scheuren, Hans; Dillenburger, Michael; Methner, Frank‐Jürgen
Abstract : For an efficient wort boiling process, a homogenous wort treatment is important. In this publication a new method for quantifying wort homogeneity is proposed. A differential equation for wort heating was formulated, which was validated by temperature measurements during the heating process. The ratio between calculation and measurements quantifies wort homogeneity. Knowing this parameter leads to a better prediction of the different reactions and processes of wort boiling. Copyright © 2015 The Institute of Brewing & Distilling